A Study of Adsorption of Modified Corn Stalk on PCP - Zhang, Jiqiang (Asian agricultural research, 2017)
The comprehensive utilization of corn stalks is an urgent agricultural and environmental problem to be solved in China.In this test,we use corn stalk as adsorbent for adsorption of PCP in water,and compare the impact of three modification methods(alkali treatment,pyrolysis,graft copolymerization) on corn stalk adsorption properties.Results show that the modified corn stalk’s adsorption of PCP is increased from 5.4 mg/g to 13.9 mg/g,17.8 mg/g and 22.5 mg/g,respectively; the corn stalk after graft copolymerization and modification has the greatest adsorption capacity; after modification,both the adsorption capacity and adsorption rate constant of corn stalk on PCP are increased significantly.